Influence of CO2 injection on the poromechanical response of Berea sandstone. (April 2020) - Tarokh, Ali; Makhnenko, Roman Y.; Kim, Kiseok; Zhu, Xuan; Popovics, John S.; Segvic, Branimir; Sweet, Dustin E.
Highlights: Methods for laboratory characterization of CO2 impact on mechanical behavior of reservoir rock are suggested. Berea sandstone was tested in pristine, heat damaged, and CO2 treated (for 22 days) damaged states. Rock mineralogy, poroelastic processes, and microseismicity during inelastic response were insignificantly affected by CO2 injection. CO2 injection decreased the strength of sandstone (10–15%) and increased porosity (10%) and permeability (up to 100%). The strongest effect of CO2 injection is on the elastic creep rate of the sandstone that increased by more than twice. Abstract: Subsurface reservoirs are targeted formations for geologic carbon dioxide (CO2 ) storage. Even if proper management of injection pressures minimizes the risks of induced seismicity, high pressure CO2 can interact with brine-saturated host rock and cause microstructural changes that lead to alterations in poromechanical properties of the rock. The effect is well pronounced in carbonate-rich rock, but observations on silica-rich reservoirs are ambiguous. In this study, we report a broad range of experiments performed on Berea sandstone, consisting mainly of quartz (∼90%), in three different states: pristine, thermally damaged, and thermally damaged then treated with liquid CO2 . Drained and undrained poromechanical tests, ultrasonic velocity measurements, acoustic emission (AE), X-ray diffraction (XRD), and petrographic analyses are conducted. The tests reveal that thermal damage alone does not significantly affect poromechanical properties. However, CO2 injection does affect strength (10–15 % decrease), permeability (up to 100% increase), porosity (10% increase), and elastic creep rate (more than twice); corresponding microstructural changes were observed from XRD test results. At the same time, the poroelastic moduli measured in triaxial compression experiments and load-induced fracture processes, as interpreted through acoustic emission data collected in uniaxial compression tests, were affected insignificantly. These experimental observations provide better understanding of the mechanical behavior of low-carbonate reservoir rocks that are subjected to high pressure CO2 injection.